Comparison of kinetic and equilibrium reaction models in simulating the behavior of porous media - Kowalsky, Michael B.; Moridis, George J. (eScholarship, University of California, 2006)
In this study we compare the use of kinetic and equilibrium reaction models in the simulation of gas (methane) hydrate behavior in porous media. Our objective is to evaluate through numerical simulation the importance of employing kinetic versus equilibrium reaction models for predicting the response of hydrate-bearing systems to external stimuli, such as changes in pressure and temperature. Specifically, we (1) analyze and compare the responses simulated using both reaction models for natural gas production from hydrates in various settings and for the case of depressurization in a hydrate-bearing core during extraction; and (2) examine the sensitivity to factors such as initial hydrate saturation, hydrate reaction surface area, and numerical discretization. We find that for large-scale systems undergoing thermal stimulation and depressurization, the calculated responses for both reaction models are remarkably similar, though some differences are observed at early times. However, for modeling short-term processes, such as the rapid recovery of a hydrate-bearing core, kinetic limitations can be important, and neglecting them may lead to significant under-prediction of recoverable hydrate. Assuming validity of the most accurate kinetic reaction model that is currently available, the use of the equilibrium reaction model often appears to be justified and preferred for simulating the behavior of gas hydrates, given that the computational demands for the kinetic reaction model far exceed those for the equilibrium reaction model.